EFEKTIFITAS MODEL EDUKASI PRAKTIK PENGASUHAN TERHADAP OPTIMALISASI TUMBUH KEMBANG BALITA - Astuti, Maya; Nurfurqoni, Fuadah Ashri (Poltekkes Kemenkes Bandung, 2024)
In Indonesia, there are still many children who are cared for inappropriately, such as neglect and violence against children, toddlers receive inappropriate care (3.69%), and toddlers experience developmental disorders (16%), both fine and gross motor development, hearing and intelligence loss, and speech delay. The child's condition cannot grow and develop optimally. The research aims to analyze the influence of the parenting practice educational model on the knowledge and growth of children under five. The educational model implemented is the result of previous survey research, so it is more appropriate to conditions in the field. This research used a pre-experimental design in Bogor City on June-August 2023 with 40 respondents. Sample criteria are mothers who have children aged 12-60 months. There were 20 people in each intervention and control group. The intervention was given seven times face to face for seven weeks. The independent variable is the educational model of caring for mothers, and the dependent variable is knowledge of caring for mothers, growth, and toddlers. The results of the Mann-Whitney test showed that there was difference in the median post-test score between the intervention and control groups in the growth variables of 5.5 points (p0.003<0.05), development of 6 points (p0.005<0.05), and knowledge of parenting practices of 10 points (p0.006 < 0.05). These data show a significant influence between the model of implementing parenting education on growth and toddlers and parenting knowledge. More education needs to be done on parenting using various media to improve the growth and development of toddlers.